Echoes of the Forest: Oral Histories from Jharkhand - Singh, Rambha; Singh, Sunil Kumar (RESEARCH HUB International Multidisciplinary Research Journal, 2026)
Jharkhand, a region endowed with dense forests, abundant minerals, and a rich indigenous heritage, has undergone profound environmental shifts over the last hundred years. Colonial forest regulations, the spread of mining and industry, infrastructure development, and climate fluctuations have all reshaped its landscapes. For communities such as the Santhal, Munda, and Oraon, forests and land have long been central to livelihood, cultural identity, and spiritual traditions. This study explores these transformations through oral histories, capturing community recollections of forest use, mining consequences, water resources, and changing livelihood practices. Adopting a qualitative framework, narrative interviews were conducted with elders, cultivators, and forest-dependent households across Hazaribagh, Ranchi, and Dhanbad. These testimonies were examined alongside historical records and policy documents to trace shifts in forest cover, biodiversity, agriculture, water availability, health, and socio-economic well-being. Respondents described earlier landscapes characterized by dense forests, sustainable resource use, and deep ecological knowledge, contrasting them with present-day challenges such as deforestation, polluted water, degraded soils, land dispossession, and livelihood insecurity. Findings highlight both fragility and resilience within local communities, revealing adaptive strategies, evolving gender roles in resource management, and ongoing efforts to safeguard ecological balance and cultural continuity. The study argues that environmental change in Jharkhand is not merely ecological but also deeply social and political. It underscores the value of oral history in amplifying marginalized voices and informing pathways toward sustainable environmental governance.